Late Male-Killing Viruses in Homona magnanima Identified as Osugoroshi Viruses, Novel Members of Partitiviridae - Fujita, Ryosuke; Inoue, Maki N.; Takamatsu, Takumi; Arai, Hiroshi; Nishino, Mayu; Abe, Nobuhiko; Itokawa, Kentaro; Nakai, Madoka; Urayama, Syun-ichi; Chiba, Yuto; Amoa-Bosompem, Michael; Kunimi, Yasuhisa (Frontiers in Microbiology, 2021)
Late male-killing, a male-specific death after hatching, is a unique phenotype found in Homona magnanima, oriental tea tortrix. The male-killing agent was suspected to be an RNA virus, but details were unknown. We herein successfully isolated and identified the putative male-killing virus as Osugoroshi viruses (OGVs). The three RNA-dependent RNA polymerase genes detected were phylogenetically related to Partitiviridae, a group of segmented double-stranded RNA viruses. Purified dsRNA from a late male-killing strain of H. magnanima revealed 24 segments, in addition to the RdRps, with consensus terminal sequences. These segments included the previously found male-killing agents MK1068 (herein OGV-related RNA16) and MK1241 (OGV-related RNA7) RNAs. Ultramicroscopic observation of purified virions, which induced late male-killing in the progeny of injected moths, showed sizes typical of Partitiviridae. Mathematical modeling showed the importance of late male-killing in facilitating horizontal transmission of OGVs in an H. magnanima population. This study is the first report on the isolation of partiti-like virus from insects, and one thought to be associated with late male-killing, although the viral genomic contents and combinations in each virus are still unknown.